2002
DOI: 10.1002/joc.797
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in temperature and precipitation over South Korea

Abstract: Temperature and precipitation changes over South Korea have been studied since 1954, both in terms of means and extreme events, using observational station data. Recurrence intervals are defined to examine trends in extreme events at each station. Generally, it is possible to describe trends in temperature and precipitation over South Korea as follows. The annual mean temperature shows an upward trend at a rate of 0.23°C decade −1 in the past four to five decades. There are some indications that climatic extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 26 publications
8
78
1
5
Order By: Relevance
“…Data such as these reveal an increase in the minimum temperatures that is greater than the increase in the maximum temperatures. Similar results were also observed by other researchers (JUNG et al, 2002;LADOCHY et al, 2007;VOSE et al, 2005), showing that although there is a high regional variability in the increase of temperature, the same tendency of an increase is evident in different parts of the globe.…”
Section: Air Temperature Changesupporting
confidence: 91%
“…Data such as these reveal an increase in the minimum temperatures that is greater than the increase in the maximum temperatures. Similar results were also observed by other researchers (JUNG et al, 2002;LADOCHY et al, 2007;VOSE et al, 2005), showing that although there is a high regional variability in the increase of temperature, the same tendency of an increase is evident in different parts of the globe.…”
Section: Air Temperature Changesupporting
confidence: 91%
“…It is well known that the air temperature over South Korea has been significantly increased due to the combined effects of increased greenhouse gases and urban heat island (Jung et al, 2002;Hong et al, 2006). Many works using observed data showed that the amount, intensity and frequency of heavy precipitation over South Korea also increased clearly (Jung et al, 2002;Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many works using observed data showed that the amount, intensity and frequency of heavy precipitation over South Korea also increased clearly (Jung et al, 2002;Kim et al, 2009). These changes of surface air temperature and heavy precipitation are closely linked with the status of lowto-mid troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…남한 역시 지난 20세기 동안 평균기온이 1.5 o C 상승하였고 (Kwon, 2005), 집중호우와 같은 극한 강우현상의 발생일수가 증가되고 있으며 강우강도 및 낙뢰강도도 강해지고 있는 것으로 보고되고 있다 (김 찬수와 서명석, 2009;명지수와 서명석, 2010;윤희정 외, 2006;Ho et al, 2003;Jung et al, 2002). 앞으 로도 계속해서 지구 평균 온도가 상승할 것으로 예 상되기 때문에 이와 관련하여 나타나게 될 평균 및 극한 기후들의 변화에 대한 관심이 점차 높아지고 있다.…”
Section: 서 론unclassified